Composting and Fermentation of Biowaste - Advantages and Disadvantages of Processes = Kompostowanie i fermentacja bioodpadów - wady i zalety procesów - Jędrczak, Andrzej (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
In 2016, in EU Member States (EU), only less than half of the biowaste produced, i.e. around 40 million tonnes, was used to produce compost and, to some extent, biogas. Most of it was still incinerated or stored together with other waste. On 14 June 2018, amendments to 6 directives on waste management were published. One of the most important changes introduced in the Waste Framework Directive is the obligation for Member States to recycle biowaste at source or selectively collect it for composting or fermentation by 31 December 2023 at the latest.
Keywords: feedstock; biowaste; composting; anaerobic digestion; surowce; bioodpady; kompostowanie; fermentacja